The Properties of Special Concrete Using Washed Bottom Ash (WBA) as Partial Sand Replacement - Mohd Sani, Mohd Syahrul Hisyam; Muftah, Fadhluhartini; Muda, Zulkifli (International Journal of Sustainable Construction Engineering and Technology, 2011)
This paper presents the use of Washed Bottom Ash (WBA) as fine aggregate in special concrete. The WBA is a waste material that is taken from electric power plant and the source material is called as bottom ash. To substitute the amount of carbon usage in concrete the bottom ash was utilized and fully submerged in water for 3 days to produce as WBA with low carbon composition. The aim of the study is to investigate the feasibility and potential use of washed bottom ash in concreting and concrete applications. The results of the physical and chemical properties of WBA were discussed. Different concrete mixes with constant water to cement ratio of 0.55 were prepared with WBA in different proportions as well as one control mixed proportion. The mechanical properties of special concrete with 30% WBA replacement by weight of natural sand is found to be an optimum usage in concrete in order to get a favourable strength and good strength development pattern over the increment ages.